A Pilot Study of a Stress Management Program for Incarcerated Veterans. Issue 11 (27th March 2021) - Sylvia, Louisa G; Chudnofsky, Rana; Fredriksson, Stacie; Xu, Bingyu; McCarthy, Megan D; Francona, Jacque; Hart, Betsy R; Millstein, Rachel; Mehta, Darshan H; Park, Elyse R; Fricchione, Gregory L
ABSTRACT: Introduction: Veterans involved in the justice system are an understudied population warranting attention given their higher risk of mental health concerns and psychosocial challenges. Thus, there is a need for programs to support the psychological health of incarcerated veterans. The present study sought to determine the acceptability and effectiveness of a mind-body stress reduction program for incarcerated veterans. Materials and Methods: Twenty-four incarcerated veterans (100% male; Mage = 44.87 (SD = 13.84)) completed a 6 week mind-body stress reduction course, or Resilient Warrior. Participants completed validated, self-report assessments of mood, functioning, mindfulness, and coping at pre- and post-program as well as having post-program qualitative feedback surveys. Results: Results showed improvement in depressive symptom severity, self-efficacy, and resilience over the study duration ( P < .05), but not stress reactivity, mindfulness, sleep disturbance, or perceived stress. The intervention was reported as helpful by 96% of participants, with 86% of participants stating they would recommend the course to others. Conclusions: The Resilient Warrior program is acceptable and well-tolerated for incarcerated veterans as well as may improve aspects of psychological health. Future studies could examine how stress reductions program might improve recidivism rates and quality of life after the release of incarcerated veterans.